2022
DOI: 10.3390/batteries8070062
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Dichalcogenides for High−Performance Aqueous Zinc Ion Batteries

Abstract: Aqueous zinc ion batteries (ZIBs) with cost—effectiveness, air stability, and remarkable energy density have attracted increasing attention for potential energy storage system applications. The unique electrical properties and competitive layer spacing of transition metal dichalcogenides (TMDs) provide dramatical freedom for facilitating ion diffusion and intercalation, making TMDs suitable for ZIB cathode materials. The recently updated advance of TMDs for high−performance ZIB cathode materials have been summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Because of this characteristic, MoS 2 have enormous potential in LIBs. 202,203 Xu et al 107 reported expanded layer of MoS 2 synthesized by exfoliation of bulk MoS 2 , which has interlayer spacing of 0.635 nm as anode materials for lithium ion batteries. The synthesized MoS 2 has higher capacity (750 mAh/g) than raw MoS 2 which has capacity of 226 mAh/g.…”
Section: Application Of 2d Mos 2 For Energy Storagementioning
confidence: 99%
“…Because of this characteristic, MoS 2 have enormous potential in LIBs. 202,203 Xu et al 107 reported expanded layer of MoS 2 synthesized by exfoliation of bulk MoS 2 , which has interlayer spacing of 0.635 nm as anode materials for lithium ion batteries. The synthesized MoS 2 has higher capacity (750 mAh/g) than raw MoS 2 which has capacity of 226 mAh/g.…”
Section: Application Of 2d Mos 2 For Energy Storagementioning
confidence: 99%
“…140 MoS 2 has been one of the earliest and most extensively studied materials for zinc-ion batteries (ZIBs) due to its unique layered structure and different phases. 151 However, unmodified MoS 2 does not exhibit ideal electrochemical performance in ZIBs. Therefore, an increasing number of researchers have begun investigating modified MoS 2 as a positive electrode material for ZIBs.…”
Section: Tmds As Cathode Materials In Batteriesmentioning
confidence: 99%
“…[54] Recently, they have studied as host Zn 2+ ions due to their some merits of the tunable layer spacing for reversible Zn 2+ insertion/extraction, numerous edge sites and sulfur vacancies for large capacity, and the high polarizability of S 2− for fast ionic transfer. [55][56][57][58] The prepared methods and electrochemical properties of transition-metal disulfides cathode materials including molybdenum disulfide, vanadium disulfide, tungsten disulfide, titanium disulfide are systematically and comprehensively summarized and discussed in this section.…”
Section: Transition-metal Disulfides Cathode Materialsmentioning
confidence: 99%